Supervising Asian International Counseling Students: Using the Integrative Developmental Model - Li, Dan; Liu, Yanhong; Lee, Injung (Journal of International Students, 2018)
This conceptual article presents an application of the integrative Asian international counseling students developmental model (IDM) as a framework for supervising Asian international counseling students in the United States. Asian international supervisees’ characteristics and needs on four developmental levels and corresponding supervision interventions are discussed. Implications for clinical supervision, counselor education, and research are provided.